2012
DOI: 10.1136/injuryprev-2012-040483
|View full text |Cite
|
Sign up to set email alerts
|

Stimulant treatment and injury among children with attention deficit hyperactivity disorder: an application of the self-controlled case series study design

Abstract: Stimulant medication use may decrease the risk of injury among children treated for ADHD, although unmeasured time varying confounding may be an alternative explanation. Injury risk may be considered during the decision-making process with regard to medication continuation among children with ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 31 publications
3
41
0
Order By: Relevance
“…We demonstrated a risk reduction for injuries among children with ADHD during periods of medication use; this risk reduction was statistically significant only for brain injuries. Recently, Raman et al 32 applied the SCCSD to The Health Improvement Network database and reported a risk reduction for injuries among 328 children with ADHD during periods of medication use. Our study covers a substantially larger sample from Germany.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated a risk reduction for injuries among children with ADHD during periods of medication use; this risk reduction was statistically significant only for brain injuries. Recently, Raman et al 32 applied the SCCSD to The Health Improvement Network database and reported a risk reduction for injuries among 328 children with ADHD during periods of medication use. Our study covers a substantially larger sample from Germany.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, treating all young ADHD patients according to WHO recommendations (Figure 1), i.e., with three pills of MPH-IR per day, yearround, with a consequent reduction in grade retention and accident rates related to untreated ADHD as suggested by Barbaresi et al 13 and Raman et al 14 respectively, would lead to savings in the region of R$ 1.163 billion/ year (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Do ADHD medications reduce school repetitions and accidents at home? Some findings are just now appearing in the literature (8).…”
mentioning
confidence: 84%